Transdifferentiation of human gingival mesenchymal stem cells into functional keratinocytes by Acalypha indica in three‐dimensional microenvironment. Issue 11 (19th June 2018) - Murugan Girija, Dinesh; Kalachaveedu, Mangathayaru; Ranga Rao, Suresh; Subbarayan, Rajasekaran
Abstract : Gingival tissue is reportedly a promising, easily accessible, abundant resource of mesenchymal stem cells (MSC) for use in various tissue engineering strategies. Human gingival MSC (HGMSCs) were successfully isolated from gingival tissue and characterized. To analyze in a two‐dimensional form, HGMSCs were cultured with basal medium and induced with 25 µg/ml of Acalypha indica . Quantitative real‐time polymerase chain reaction (qPCR) and western blot analysis showed the presence of keratinocyte‐specific markers, including cytokeratin‐5 and involucrin. To further assess its capability for stratification akin to human keratinocytes, HGMSCs were encapsulated in a HyStem ® ‐HP Cell Culture Scaffold Kit and cultured in the presence of A. indica . Calcein AM staining indicated that the HyStem ® ‐HP Scaffold Kit has excellent biocompatibility. Immunofluorescence and qPCR analysis revealed the presence of keratinocyte‐specific markers. The study concluded that the three‐dimensional microenvironment is a novel method for inducing epidermal differentiation of HGMSCs to engineer epidermal substitutes with the help of A. indica, which provides an alternative strategy for skin tissue engineering. Abstract : Human gingival tissue was successfully processed for the isolation of human gingival mesenchymal stem cells, which on induction with methanol extract of Acalypha indica differentiated into functional keratinocytes in vitro. Further encapsulation in the three‐dimensional microenvironment did not affect their functional gene expression, suggesting the potential for differentiation into a physiologically active organotypic culture.